2013
DOI: 10.1590/abd1806-4841.20132072
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis, food allergy and dietary interventions. A tale of controversy

Abstract: Atopic Dermatitis has long been a controversial entity in regard its relationship to food allergy. Indeed, inter-discipline disparity in the way dermatologists and allergologists perceive the food allergy/atopic dermatitis interplay, hampers the design of concise therapeutic strategies and conveys conflicting messages to the patients. Within this conceptual frame, food exclusion regimes are rendered a contentious option. On the basis of this acknowledgment, we opted to put the emphasis on the discrepant percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Participants’ perception that parents are seeking an underlying cause for their child’s eczema, and struggle to source reliable online information, concurs with previous surveys and qualitative studies with parents. 9 , 29 , 30 GPs in this study expressed uncertainty about referral for allergy testing or trial of exclusion diets which reflects both the controversy around the role of allergy in eczema, 31 , 32 the limitations of allergy testing currently available, 33 , 34 and the poor evidence base for exclusion diets in patients with eczema. 34 , 35 Despite the lack of evidence, dietary manipulation by parents is common, with up to 75% of parents trying dietary exclusions (49% unsupervised), and 41% dietary supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…Participants’ perception that parents are seeking an underlying cause for their child’s eczema, and struggle to source reliable online information, concurs with previous surveys and qualitative studies with parents. 9 , 29 , 30 GPs in this study expressed uncertainty about referral for allergy testing or trial of exclusion diets which reflects both the controversy around the role of allergy in eczema, 31 , 32 the limitations of allergy testing currently available, 33 , 34 and the poor evidence base for exclusion diets in patients with eczema. 34 , 35 Despite the lack of evidence, dietary manipulation by parents is common, with up to 75% of parents trying dietary exclusions (49% unsupervised), and 41% dietary supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…Deprivation of suspected foods in individuals with AD for whom there is no diagnosis of food allergy does not benefit the dermatitis and should be avoided. The review by Guibas et al [36] also highlighted the same critical issues reported in the literature on AD and food allergies. Although some patients report exacerbation of AD after intake of certain foods, nutritional restrictive measures often taken on their own initiative by patients are not effective.…”
Section: Atopic Dermatitismentioning
confidence: 81%
“…Na Categoria 1 (fatores ambientais), os relatos das mães de crianças com DA a respeito de fatores desencadeantes do surgimento e/ou exacerbação dos sintomas estão de acordo com o que está descrito na literatura de doenças crônicas de pele, independentemente do perfil clínico da criança encontrado no CBCL. A literatura destaca, como possíveis fatores ambientais desencadeantes da DA, o contato com aeroalérgenos, colonizações bacterianas, produtos de limpeza e higiene, mudanças climáticas, alimentação, deficiência de vitamina D e presença de distúrbios emocionais nos cuidadores de crianças com dermatoses (Gon et al, 2013;Guibas, Gregoriou, Makris, Rigopoulos, & Chliva, 2013;Lipnharski, Bessa, Azevedo, Bonamigo, & Quinto, 2013;Manzoni et al, 2013;Mesquita, Costa, & Igreja, 2013;Rodrigues, Montealegre, Pires, Melo, & Hahnstadt, 2011). Esses fatores foram identificados nos relatos das mães de crianças com DA, tais como: "verão assim é muito frequente devido à transpiração na dobra", "alimentos como chocolate, peixes e frutos do mar" (sic).…”
Section: Discussionunclassified